Influência do vírus da hepatite G (GBV-C) na resposta imune frente à infecção por Leishmania chagasi - Lima, Josane Regina de (2001)
GB virus type C (GBV-C) appears to promote a Th1 response and is associated with prolonged survival in HIV-infected people. L. chagasi causes a spectrum of illness that varies from severe visceral leishmaniasis, a disease that in the majority of cases is fatal if not treated, to self resolution of infection and development of positive DTH response that is protective against symptomatic disease. To determine if GBV-C viremia might influence the outcome of Leishmania infection, we characterized GBV-C status in a cohort of subjects residing in a L. chagasi endemic area in Brazil. GBV-C viremia was more prevalent in blood donors from urban than in periurban regions of Natal, Brazil (16% and 7.5% respectively). Evidence of prior GBV-C (anti-E2 antibodies) was detected in 24% and 12%of these groups respectively. Anti-E2 increased with age (p= 0.0121). No difference in GBV-C viremia was found in the DTH+ and VL groups (p= 0.269); however, subjects with visceral leishmaniasis were more likely to have anti-E2 than DTH+ subjects (p=0.0012), and DTH induration was smaller in subjects with E2 antibodies (4.5 mm) compared those without (7.12 mm) (p= 0.002). Furthermore, the size of the Leishmania DTH response was greater in GBV-C viremica subjects (6.8 mm) compared to non-viremic subjects (3.3 mm; p= 0.0054). There findings suggest that GBV-C virus may promote a type 1 immune response that could influence the outcome of Leishmania infection